Analisis Pengaruh Tarif,Kualitas Pelayanan dan Kepuasan Konsumen Terhadap Loyalitas Konsumen Pada PO.Rosalia Indah di Surakarta - Ibrahim, Nanang Khairul, Drs. M. Nasir, M.M (2017)
The purpose of this study was to determine the effect of price, quality of service and customer satisfaction on consumer loyalty on a beautiful PO.Rosalia In Surakarta. In this study, the sampling technique used is purposiv Sampling. Data types and sources of data in this study using primary data obtained from the respondents that are the result of filling out the questionnaire. Data analysis techniques used are validity with all the variables declared valid by the value corrected item-total correlation of each variable above 0.256, reliability test with the test results of this study each variable is declared reliable by Cronbach Alpha above 0.600. With the criteria that the variable rate is negative and no significant effect on consumer loyalty, while the quality of service and customer satisfaction is positive and significant effect on consumer loyalty, hypothesis testing by t-test at variable rates is not significant, while in the variable quality of service and customer satisfaction significantly , From the calculation of F Test F> F table (19.236> 2.76) means that together variable rates, service quality and customer satisfaction have a significant effect on consumer loyalty. shows that the results of the analysis of data obtained R square (R2) of 0.375, meaning variation change of 0.375 Consumer Loyalty variables can be explained by the variable price, quality of service, customer satisfaction have a significant effect on consumer loyalty of 37.5%. While the rest of 62.5% is explained by other variables outside the model